Complying with conservation compliance? An assessment of recent evidence in the US Corn Belt - Austin Holland; David Bennett; Silvia Secchi (Environmental Research Letters, 2020)
Conservation provisions of US farm bills since 1985 have been aimed at mitigating negative environmental impacts of US agriculture. One of the long term goals has been to protect against soil erosion, with a focus specifically on highly erodible land (HEL). Conservation Compliance (CC) mandates that, in order to receive federal subsidies, farmers who plant annual crops on HEL must implement a conservation plan, with practices such as rotating crops and no-till farming. When crop prices increase, however, the incentives not to follow the plan increase, as conservation activities can reduce farmers’ profits. This study is the first to assess the performance of conservation compliance between 2007 and 2019, a period of historically high and variable crop prices, using geographical information system tools and crop data in a critical agricultural production region, the US Corn Belt. Our results indicate there was a substantial increase in continuous corn on HEL, a proxy measure for non-compliance, in several portions of the study area in correspondence with higher crop prices following the 2007 Energy Bill. This mirrored the change in crop rotations on all cropland. The increase was positively correlated with both absolute and relative corn prices. While at the height of absolute and relative corn prices there were increases in continuous corn on HEL everywhere across the study region except parts of Missouri, some of the largest changes occurred in environmentally sensitive regions and areas which use irrigation, thereby potentially creating disproportionate environmental impacts. Similar changes in continuous corn also occurred in all cropland in the region, indicating that mandatory conservation programs are as vulnerable to periods of high crop prices as voluntary programs. Better monitoring for both CC and other conservation programs is critical to ensure the policies work as intended.